Dehydration-Responsive Element Binding Protein 1C, 1E, and 1G Promote Stress Tolerance to Chilling, Heat, Drought, and Salt in Rice - Wang, Huanhuan; Lu, Shan; Guan, Xiangyu; Jiang, Yuan; Wang, Bin; Hua, Jian; Zou, Baohong (Frontiers in Plant Science, 2022)
The dehydration-responsive element binding protein 1 (DREB1)/C-repeat-binding factor (CBF) genes are key regulators of cold acclimation and freezing tolerance in the chilling tolerant Arabidopsis thaliana. Here, we investigated the function of three members of the 10 rice DREB1 genes, OsDREB1C, E, and G, in the chilling sensitive rice plants. Their loss of function (LOF) mutants were each more chilling susceptible compared to the wild type, and the LOF mutants of all three genes, dreb1ceg, were more chilling susceptible than any of the single mutants. Strikingly, these mutants were capable of cold acclimation, indicating that these rice DREB1 genes are important for basal chilling tolerance but not cold acclimation. Transcriptome and physiology analyses suggest that the OsDREB1C/E/G genes are involved in reactive oxygen species (ROS) scavenging and cell death regulation under chilling. Furthermore, these three rice DREB1 genes are found to promote tolerance to other abiotic stresses: the OsDREB1C/E/G genes are positive regulators of heat tolerance, OsDREB1C and OsDREB1G are positive regulators of salt tolerance, and OsDREB1G is a positive regulator of drought tolerance. These findings expand our knowledge of the roles of DREB1 proteins in plants, enhance our mechanistic understanding of abiotic stress tolerance and will facilitate the generation of stress-tolerant crop plants.